Mathematical modelling and optimization of catalytic dewaxing of diesel oil cuts and atmospheric gas oil; Petroleum and Coal; Vol. 58, iss. 1 - Belinskaya N. S. Natalia Sergeevna (2016, 2016)
Title screen